Cloning an RBD-T4-LINKER-C5a sequence encoding the SARS-CoV-2 antigen into a plant expression vector - Tue, Nguyen Hoang; Luong, Nguyen Ngoc; Tien, Nguyen Quang Duc (Hue University Journal of Science: Natural Science, 2023)
This study aims to make a plant expression vector with an RBD-T4-Linker-C5a sequence that codes for the SARS-CoV-2 antigen and an A3Dsp signal peptide from the rice 3D amylase gene located before the RBD. Methods of molecular cloning were applied in this study. The plant expression vector pNHL22 harboring the RBD-T4-Linker-C5a sequence was successfully established and conjugated into Agrobacterium tumefaciens LBA4404 by triparental mating. Bacteria A. tumefaciens containing the RBD-T4-Linker-C5a sequence are now ready for genetic transformation into the Nicotiana benthamiana plant for future applications.